Effect on growing of Bali cattle with difference ages raised in cages - Harapin Hafid (Talenta Publisher, 2021)
This study aimed to obtain information on the influence of age differences on the growth of Bali cattle that are traditionally reared in cages. The number of cattle used was nine heads. During the study, individual cages were used. This study had a randomized block design with three ranges of body weight as a group. The treatment in this study was the difference in the age of cattle, which consisted of cattle aged one year (I1), age two years (I2), and three years (I3). The results showed that the difference in the age of the cattle had no significant effect (P> 0.05) on the dry matter consumption of feed, daily body weight gain, and the conversion of Bali cattle feed traditionally reared in pens. However, there is a tendency that cattle aged one year have better growth and efficiency in using feed than cattle aged 2 and 3 years. It can be concluded that raising cattle at one year of age results in more efficient growth than cattle at 2 and 3 years. However, further testing needs to be done with more cattle and a more comprehensive range of body weight.